Tantangan dan Hambatan dalam Implementasi Bela Negara di Perguruan Tinggi - Adiwinata, Syan Rosyid; Febryanti, Dita Indra; Vasthi, Respati Prajna (Universitas Pendidikan Ganesha, 2025)
Based on the Fund for Place survey regarding the global vulnerability index, data shows that Indonesia is currently in the 99th place out of 178 countries in the world. In this case Indonesia gets a warning as its predicate, and one day can be included in the high warning level. Indonesia's lower position in the global vulnerability index is nothing but due to the low participation of the younger generation in the implementation of state defense. This study aims to identify, process, and analyze data empirically about the challenges and obstacles of state defense attitude in University and their solution recommendations. This study uses quantitative descriptive methods, because this study will describe the current situation systematically and factually with the aim of analyzing data by describing or describing data that has been collected as a solution to research problem.